2004
DOI: 10.1258/00236770460734362
|View full text |Cite
|
Sign up to set email alerts
|

The bedding of laboratory animals as a source of airborne contaminants

Abstract: SummaryIn work environments with laboratory animals, the bedding of animals binds the excreta as well as other compounds originating from the animals and their environment. These may be generated into the ambient air when the personnel handle bedding in different procedures. This study compares the dustiness of different types of six clean and four soiled beddings from rat or mouse cages. The dust generation of clean bedding varied from <1 to 25 mg=m 3 . When used in the cages of rats or mice for 4 days, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 19 publications
(16 reference statements)
3
28
1
1
Order By: Relevance
“…These results are surprising because aspen is generally regarded as relatively nontoxic, but to our knowledge, all previous relevant studies have been brief, and did not use a paper bedding comparable with AlphaDri or Omega-Dri (Tö rrö nen et al 1989, Odynets et al 1991, Holland & Griffin 2000. The histological analysis did not allow us to identify the agent responsible for the pathology, but candidates could include: (a) microorganisms inherent in the material (Ewaldsson et al 2002, Kaliste et al 2004; (b) toxic volatile substances associated with the source material or processing products (Tö rrö nen et al 1989, Odynets et al 1991; and (c) cellulose dust (Milton et al 1990, Tatrai et al 1995, Kaliste et al 2004). Ammonia was not the cause because it neither differed with bedding type nor correlated with sneezing or respiratory pathology.…”
Section: Discussionmentioning
confidence: 99%
“…These results are surprising because aspen is generally regarded as relatively nontoxic, but to our knowledge, all previous relevant studies have been brief, and did not use a paper bedding comparable with AlphaDri or Omega-Dri (Tö rrö nen et al 1989, Odynets et al 1991, Holland & Griffin 2000. The histological analysis did not allow us to identify the agent responsible for the pathology, but candidates could include: (a) microorganisms inherent in the material (Ewaldsson et al 2002, Kaliste et al 2004; (b) toxic volatile substances associated with the source material or processing products (Tö rrö nen et al 1989, Odynets et al 1991; and (c) cellulose dust (Milton et al 1990, Tatrai et al 1995, Kaliste et al 2004). Ammonia was not the cause because it neither differed with bedding type nor correlated with sneezing or respiratory pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in laboratory animal facilities showed that type of bedding materials applied can influence allergen exposure levels. 11,12 This prompted us to hypothesize that bedding materials might be a significant determinant for bioaerosol exposure in cow barns as well.…”
Section: Introductionmentioning
confidence: 99%
“…By the end of the fattening period, straw bedding became more "dusty" as it was more dirty, disintegrated, and could potentially generate more particles (Aarnink et al, 2004). Type of litter and moisture content may also affect PM concentrations (Kaliste et al, 2004).…”
Section: Source Apportionment Of Pmmentioning
confidence: 99%
“…In pig houses, higher PM concentrations are found in systems with bedding than in those with concrete floors (Aarnink et al, 2004). Type of litter and moisture content may also affect PM concentrations (Kaliste et al, 2004).…”
Section: Factors Affecting Pm Generation and Levelsmentioning
confidence: 99%
See 1 more Smart Citation